Effects of consensus on Leader–Member Exchange (LMX) within nursing teams on the relationship between abusive supervision, job satisfaction, and unit turnover: A multilevel moderation study - Caputo, A.; Costa, P.; Gatti, P.; Cortese, C. G.; Ferreira, A. I. (Journal of Nursing Management, 2025)
Aim: This study explores how consensus on leader–member exchange (LMX)—the degree of within-unit agreement regarding the LMX nurse leaders establish with each team member—moderates the effects of abusive supervision on job satisfaction and internal turnover intentions. Method: Involving a sample of 1357 nurses nested into 130 groups (led by as many nurse leaders), cross-level moderations were tested. Results: Results show that, on one hand, LMX consensus acts as a resource when it is stronger, dampening the effect of abusive supervision on job satisfaction. On the other hand, nurses with higher job satisfaction belonging to groups with higher LMX consensus report higher intentions to change wards than nurses in groups with lower LMX consensus. The discussion addresses the concept of “star employees,” i.e., employees with better performance, visibility, and relevant social capital. Implications for Nursing Management: The discussion highlights the importance for nurse managers to consider both the quality of individual LMX and overall team consensus to enhance nurse well-being and reduce turnover intentions.